Weldability of Grade 2 Titanium Sheets with Pulsed Nd:YAG Microlaser Welding Filler and Without Filler - Serkan APAY (Medžiagotyra, 2021)
Laser welding method is widely used in the welding of different materials. Deep penetration, low heat input, narrow heat affect zone, low stress-strain, and distortion are important features of this welding method as compared to other joint methods. Today, it is possible to see the applications of laser welding in the repair of precious metals, moulds, and machine parts. The laser welding method is preferred in the manufacture of many parts of precious metals. Titanium and particularly Grade 2 alloys are used in a wide range of applications, from medical applications to the aerospace industry applications. Since titanium is made of precious metals, it is of great use in manufacturing without much scrap. In the joints made by welding, it is estimated that the amount of scrap loss will decrease as a result of the potential to predict the distortion that the material will undergo and to provide more controlled planning of the current production. In this study, the weldability of 0.6 mm sheet materials with laser butt-welding was investigated. The effects of pulsed micro laser welding parameters on the microstructure, mechanical properties, and surface morphology of the fractures were investigated. As a result of the microstructure examination, it was found that cross-section narrowing was seen without filling welding. Fracture of the welded joints occurred in the base metal, showing an ultimate tensile strength of approximately 248 MPa with an elongation of 26.7 %.